The application of landscape elements for an interior landscape - Maulad Zakariya, Nurul Fatihah; Muhammad Usman, Nurul Hidayah; Mohd. Hussain, Mohd. Ramzi (2015)
Interior landscape is the art and science of organizing landscape elements within enclosed spaces. In order to improve and enhance the appearance of the indoor environment which is similar to outdoor landscape, a combination of landscape elements in interior landscape is applied. The paper disscuss on the application of landscape elements for an interior landscape and this research is seeking answers by understanding the crucial of hardscape and softscape elements in contributing to space decoration, visual appearance, acoustic, aesthetic value and thermal comfort. The aim of the paper is to identify the application and uses of landscape elements for interior landscape while the main objective of the research is to study the importance of landscape elements for interior landscape. The research was conducted in Petaling Jaya area which is PJ Trade Centre, The Curve Shopping Mall Mutiara Damansara and Empire Damansara, a building that provide the combination of hardscape and softscape elements in an interior space. The research employs a quantitative and qualitative approach that consists of questionnaire survey, observation, interview and taking photographs. The result shows that landscape elements which are hardscape and softscape are a complement to interior landscape in contributing to healthy indoor environment. Hence, it is hope that the application of landscape elements is not only contribute to the space but it can integrate the environment, nature and man together.